Evaluation of Nitric Acid Extraction of Elements from Soils and Sediments in Two watersheds in East Tennessee. Issue 11 (17th June 2019) - Huangfu, Yanchong; Essington, Michael E.; Hawkins, Shawn A.; Walker, Forbes R.; Schwartz, John S.; Layton, Alice C.; Hull, Robert A.
ABSTRACT: Determining the total elemental concentrations of soils requires a total dissolution method, in which hydrofluoric acid (HF) is commonly used. However, this method is tedious and risky due to the dangerous reagent HF. This study compared a single acid extraction technique using a nitric acid (HNO3 ) extraction method to total dissolution (HF + microwave assisted aqua regia ) for evaluating the total elemental concentrations in soils and sediments. The two methods were used to analyze the elemental content of soils and sediments from the Oostanaula Creek and Pond Creek watersheds in East Tennessee. Twenty-one elements (Al, Ba, Ca, Co, Cr, Cu, Fe, K, La, Li, Mg, Mn, Nd, P, S, Si, Sr, Ti, V, Zn, and Zr) were subsequently measured using inductively coupled plasma optical emission spectrometry (ICP-OES). The extraction efficiency for HNO3 relative to the total was compared and discussed. In general, HNO3 can extract the elements in absorbed phases and those residing in non-silicate minerals. Six elements (Ba, Co, Fe, Ca, Mn, and P) generated significant correlations between total and HNO3 in both OC and PC watersheds. Finally, the elements were grouped according to the interrelationships of their total elemental concentrations based on the dendrogram plots, suggesting their geochemical association in soils and sediment forming minerals.